How Pesantren Can Be Economically Independent: A Literature Review - anwar, mustofa; Fatiha, Belgheddouche; Puspitasari, Ema (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2024)
Pesantren has a very big role in creating a superior and character-building generation in the nation. Since the beginning of the birth of Pesantren, the independence of Pesantren as a religious educational institution has not been in doubt. This study aims to synthesize the results of research on the economic independence of Islamic boarding schools to explore the research findings. So, it was obtaining a formula to realize the independence of Islamic boarding schools. This study is a literature review by using content analysis on a number of articles that have been published in various journals using Mendeley Searches with the keyword “Economic Independence of Islamic Boarding Schools” in the three-year range 2021-2023. These research steps adopt the theory developed by Francis & Baldesari (2006). Data obtained from Mendeley Searches was selected according to the research theme. Next, a content analysis is carried out. The findings of this study show that pesantren has the potential to achieve economic independence. The potential is elected from within the pesantren and outside the pesantren. There are several factors that can be implemented to realize the independence of pesantren, namely internal factors and external factors. This study also found measures that can be applied to realize the economic independence of pesantren in a sustainable manner